Ultrasound-Assisted Extraction of Antimalarial Compounds from the Bidara Laut (Strychnos ligustrina) Heartwood - Sri Familasari; Rita Kartika Sari; Wasrin Syafii; Anne Carolina; Umi Cahyaningsih; Siti Sa'diah (Jurnal Sylva Lestari, 2023)
The aqueous wood extract of bidara laut (Strychnos ligustrina) from maceration demonstrated the greatest antimalarial activity against Plasmodium falciparum strain 3D7. However, this method has several limitations, including a lengthy extraction time, which allows for microorganism contamination. The aim of this study was to quantify the yield, evaluate the antimalarial effectiveness of the P. falciparum growth in-vitro, and analyze the aqueous bidara laut heartwood extracts phytochemical composition from the two different extraction methods,  namely the method of maceration extraction for 24 hours and the ultrasound-assisted extraction (UAE) for 30 (UAE30), 45 (UAE45), and 60 (UAE60) minutes. The bidara laut heartwood extract from the UAE60 method had relatively similar yield and antimalarial activity with the bidara laut heartwood extract from the UAE45 method. However, these extracts had higher yield and antimalarial activity than the extracts from the maceration and the UAE30 methods. The results of LC-MS/MS analysis revealed that the main compounds in the UAE45 and UAE60 extracts were strychnine, quinaprilat, and 3,4-bis-cyclobut-3-ene-1,2-dione, which has potent antimalarial properties. Keywords: antimalarial activity, Plasmodium falciparum, quinaprilat, strychnine, Strychnos ligustrina